Pablo GONZÁLEZ TORNEL (dir.), «Disseny, seda i flors» / «Diseño, seda y flores», Gijón, Ediciones Trea, 2022, 344 págs. - Molina Martín, Álvaro (Cuadernos de Estudios del Siglo XVIII, 2023)
Sin resumen.